States' Third Five Year Plan: Outlay, Resources and Targets: (An Assessment) - Planning Commission, Government of India (Planning Commission, Government of India, 1965)
The Third Five-Year Plan (1961–1966) of India outlines financial outlays, resource allocations, and sectoral targets, emphasizing agricultural production, irrigation, power generation, and social services. With a projected plan outlay of Rs 4,000 crores and an Annual Plan expenditure of Rs 1,053 crores for 1965-66, states demonstrated varied performance in fund utilization. While some states like Andhra Pradesh, Maharashtra, and West Bengal exceeded expenditure targets, Bihar and Madhya Pradesh lagged. Agricultural targets faced mixed results, with shortfalls in foodgrain production but surpassing projections for cash crops in certain regions. Irrigation and power sectors experienced delays due to cost escalations and construction slowdowns, while social services showed moderate progress, with education outlays exceeding targets. Overall, the plan reflects achievements alongside significant inter-state disparities, highlighting the need for focused resource mobilization and project execution strategies.
Planning Commission Programme Administration Division
Keywords: Third Five Year Plan-India- States; Agricultural Production; Irrigation Development; Power Generation; Social Services; State Performance; Resource Allocation